(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
The field experiment was conducted at Nabogram Agro Farm, Mannannagar, Sadar, Noakhali during the period from October 2020 to January 2021 to evaluate the effect of different organic fertilizers on the growth and yield of broccoli (Brassica oleraceae var. italica). The experiment was laid out in a Randomized Complete Block Design (RCBD) consisting of five treatments with three replications. The five treatments were T0 (No manure), T1 (Cowdung 5 t ha-1), T2 (Trichocompost 5 t ha-1), T3 (Vermicompost 5 t ha-1), T4 (Cowdung 50% + Trichocompost 50%) and T5 (Cowdung 50% + Vermicompost 50%). Data were collected in respect of plant growth and yield indicating characters at harvest. All the recorded parameters were statistically significant. For 100% curd initiation, maximum time (61 days) was recorded from T0 (Control), while minimum days (55 days) were recorded from T2 (Trichocompost 5 t ha-1). At harvest, the maximum plant height (64.70 cm), leaf length (35.05 cm), leaf breadth (32.32 cm), number of leaves per plant (14.66), the weight of full plant (1158.27 g), the marketable weight of curd (496.67 g), individual curd weight (320.67 g), diameter of curd (13.432 cm), marketable yield (19.242 t ha-1) were found in treatment T5 (Cowdung 50% + Vermicompost 50%) whereas lowest data recorded from treatment T0 (Control). So it is observed that T5 (Cowdung 50% + Vermicompost 50%) provides the highest results which may be more economical for the farmer according to the findings of this experiment. Vol. 10, No. 3, December 2023: 237-245